Internalisasi Nilai Karakter Anak melalui Kegiatan Pembelajaran Agama Rutin: Studi Kasus di Desa Labuan Toposo, Sulawesi Tengah - Widyawati, Widyawati; Hidayat, Nur (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2025)
This study aims to explore the process of internalizing religious character values among children aged 7–12 years through regular Islamic learning activities held every Saturday and Sunday evening in Labuan Toposo Village. Employing a qualitative approach with a case study method, data were collected through eight weeks of participant observation, in-depth interviews with one main teacher-facilitator and 12 child participants, as well as visual documentation of the activities. The findings reveal that these activities effectively instill essential values, including patience, sincerity, responsibility, empathy, cooperation, gratitude, and piety. The teacher-facilitator implemented various reflective and adaptive strategies, including role modeling, value-based discussions, positive reinforcement, age-appropriate methods, and creative activities such as assembling puzzles and crafting miniature Ka'bah models. These strategies help children not only understand values cognitively but also internalize and apply them in their daily lives. In addition to observed behavioral changes during the sessions, children began to show positive initiatives at home, such as praying diligently, helping parents, and reminding siblings or friends to do good deeds. The study also identified challenges, including limited learning resources, irregular attendance, and the burden of having only one facilitator, which were addressed through participatory and contextual approaches. These findings highlight the importance of interactive, reflective, and contextually grounded community-based Islamic learning as an effective strategy for character education, particularly in rural settings.